2020
DOI: 10.3892/ijmm.2020.4668
|View full text |Cite
|
Sign up to set email alerts
|

Activation of SIRT1 promotes cartilage differentiation and reduces apoptosis of nucleus pulposus mesenchymal stem cells via the MCP1/CCR2 axis in subjects with intervertebral disc degeneration

Abstract: Intervertebral disc degeneration (Idd) is a condition involving disruption of the bone tissue distribution. Nucleus pulposus mesenchymal stem cells (NPMScs) and Sirtuin 1 (SIRT1) play important roles in bone diseases, therefore the aim of the present study was to evaluate the roles of SIRT1 and NPMScs in Idd. First, NPMScs were harvested from patients with Idd. Then, the NPMScs were treated with a SIRT activator, and monocyte chemoattractant protein 1 (McP1) and chemokine receptor 2 (ccR2) inhibitors. Indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Immune cells are widely involved in the occurrence and development of skeletal degenerative diseases 20 . Studies have shown that degraded nucleus pulposus and annulus brosus produce a large number of pro-in ammatory factors, including IL-1α, IL-β, TNF-α, and C-C motif chemokine ligand (CCL) 21 . These in ammatory chemokines further recruit immune cells to in ltrate the intervertebral disc, exacerbating the in ammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells are widely involved in the occurrence and development of skeletal degenerative diseases 20 . Studies have shown that degraded nucleus pulposus and annulus brosus produce a large number of pro-in ammatory factors, including IL-1α, IL-β, TNF-α, and C-C motif chemokine ligand (CCL) 21 . These in ammatory chemokines further recruit immune cells to in ltrate the intervertebral disc, exacerbating the in ammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…To identify favorable factors driving anti-inflammation and regeneration, we examined one of the important factors, Sirt1, involved in cartilage repair. Recently, it has been reported that Sirt1 promotes chondrogenic differentiation and reduces MSC apoptosis (Ou et al, 2020). In addition, activation of Sirt1 inhibits inflammation and degradative processes in cartilage (Backesjo et al, 2009;Buhrmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…studies investigating naturally occurring canine 7,40 and (painful) human [41][42][43][44][45][46][47][48][49][50][51] IVD degeneration. Interestingly, several of these factors have been associated with MCs 52 and nerve sprouting within the IVD tissue resulting in discogenic pain.…”
Section: Interleukins Chemokines and Other Inflammatory Mediatorsmentioning
confidence: 99%